Examining the Management Impact: A Literature Review on the Phasing Out of Cheques in South Africa - Abrahams, Estelle Deseree (Ilomata International Journal of Tax and Accounting, 2025)
The South African Reserve Bank, along with other financial authorities, announced that as of December 31, 2020, the acceptance or issuance of cheques as a valid form of payment would cease. This study seeks to explore the management implications of this decision, considering the developing economic landscape of this country. A qualitative approach was employed, utilizing existing literature to gain insights into the potential impact of discontinuing cheques. The findings suggest that changes will be necessary for businesses and financial houses to accommodate new digital payment solutions and educate vulnerable persons. source documents, impacting the resolution of discrepancies.